2019
DOI: 10.1177/0734242x19890647
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of biomass catalytic depolymerisation conditions by using response surface methodology

Abstract: The aim of this study is to present the optimum operating conditions for reducing energy consumption in the process of obtaining bio-oil from the mixture of sawdust, waste lubricating oil, lime, and commercial catalyst. In the study where the catalytic pressureless depolymerisation (also called Katalytische Drucklose Verölung – KDV) was applied, the operating conditions were analysed with response surface methodology. According to the analysis of variance results, a mathematical model was obtained for specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The effect of the interaction of four factors (A, B, C, and D) on Y was intuitively reflected by observing the steepness, contour density, and contour presentation shape of the 3D surface map [ 27 ]. Figure 4 shows that Y tended to increase and then decrease with increasing factor levels when A, B, C, and D interacted with any two factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the interaction of four factors (A, B, C, and D) on Y was intuitively reflected by observing the steepness, contour density, and contour presentation shape of the 3D surface map [ 27 ]. Figure 4 shows that Y tended to increase and then decrease with increasing factor levels when A, B, C, and D interacted with any two factors.…”
Section: Resultsmentioning
confidence: 99%
“…A portion of the data were used to train the BP-ANN model and the remaining portion was used for testing and validating the model [ 27 ]. The relationship of the regression fit between the actual and predicted values are shown in Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
“…To visualize the effect of the interaction between the ultrasonic factors on Y, the 3D surface charts were drawn (Figure 4) [18]. The steeper surface and the higher slope indicate a stronger influence of the interaction between two factors on gutta-percha purity [19]. It could be observed that the interaction between frequency (X 1 ) and temperature (X 4 ) and that between power (X 2 ) and temperature (X 4 ) had greater impacts on the removal of plant tissue fragments.…”
Section: Bbd Optimization and Verification Of Ultrasonic Parametersmentioning
confidence: 99%